Acetylation of Wood Flour from Four Wood Species Grown in Nigeria Using Vinegar and Acetic Anhydride. (10th January 2013) - Azeh, Yakubu; Olatunji, Gabriel Ademola; Mohammed, Cheku; Mamza, Paul Andrew
Abstract : Effect of acetylation on pretreated wood flour of four different wood species, Boabab ( Adansonia digitata ), Mahoganny ( Daniella oliveri ), African locust bean ( Parkia biglobosa ) and Beech wood ( Gmelina arborea ), had been investigated. The first batch of wood species were acetylated using acetic anhydride while the second batch were acetylated with commercial vinegar. Both experiments were conducted in the presence of varying amount of CaCl2 as catalyst and at temperature of 120°C for 3 h. The success of acetylation was determined based on Weight Percent Gain for each sample treated with either chemicals used. FT-IR, a veritable tool was used for the analysis of both treated and untreated samples to further investigate the success of acetylation. The results showed the presence of important band such as carbonyl absorptions at 1743, 1744, 1746, 1731, 1718 and 1696 cm −1 as appeared separately in the spectra of acetylated samples, confirming esterification occurred. The purpose of this work was to investigate the applicability of vinegar for acetylation of lignocellulosic fibers. Blends/composites were prepared by solution casting and their kinetics investigated in distilled water. The results indicated they could be used in outdoor applications such as, decking and packaging.